Ecological consequences of contrasting dispersal syndromes in New World Ephedra: higher rates of niche evolution related to dispersal ability. Issue 12 (21st April 2015) - Loera, Israel; Ickert‐Bond, Stefanie M.; Sosa, Victoria
Abstract : In this study we selected the New World species of Ephedra to understand the ecological consequences of different dispersal syndromes. The twenty‐three species of Ephedra in the New World have a disjunct distribution in North and South American arid and semi‐arid habitats, exhibiting three dispersal syndromes related to dispersal by birds, wind and rodents. Using DNA sequence data we inferred phylogenetic relationships and lineage divergence times, and used these estimates to test different ecological assumptions. Using comparative methods we tested for correlations between dispersal syndromes and a set of ecological variables (niche breadth, niche evolution, distributional ranges and niche position). We found that speciation events in the New World coincided with the expansion of arid habitats in this region. We suggest that the bird dispersal syndrome is related with higher rates of climatic niche evolution for all variables used, including aridity index, mean annual temperature and mean annual precipitation. Distribution ranges were correlated with niche breadth, they were however not significantly different between dispersal syndromes. Species inhabiting the extremely arid regions on niche axes had narrower niche breadths. We conclude that species whose seeds are dispersed by birds have colonized a broader set of habitats and that those with wind and rodent dispersal syndromes might have promoted the colonization of more arid environments.